A nanoluciferase SFTSV for rapid screening antivirals and real-time visualization of virus infection in miceResearch in context - Huan Xu; Xiaoqin Jian; Yuxi Wen; Mengwei Xu; Runming Jin; Xiaoyan Wu; Fen Zhou; Junyuan Cao; Gengfu Xiao; Ke Peng; Yuanchao Xie; Hongbo Chen; et al. (EBioMedicine, 2024)
Summary: Background: Severe fever with thrombocytopenia syndrome virus (SFTSV) is an emerging tick-borne pathogen that causes severe hemorrhagic fever in humans, but no FDA-approved specific antivirals or vaccines are available to treat or prevent SFTS. Methods: The plasmids construction and transfection were performed to generate the recombinant SFTSV harboring the nanoluciferase gene (SFTSV-Nluc). Immunostaining plaque assay was performed to measure viral titers, and DNA electrophoresis and Sanger sequencing were performed to evaluate the genetic stability. Luciferase assay and quantitative RT-PCR were performed to evaluate the efficacy of antivirals in vitro. Bioluminescence imaging, titration of virus from excised organs, hematology, and histopathology and immunohistochemistry were performed to evaluate the efficacy of antivirals in vivo. Findings: SFTSV-Nluc exhibited high genetic stability and replication kinetics similar to those of wild-type virus (SFTSVwt), then a rapid high-throughput screening system for identifying inhibitors to treat SFTS was developed, and a nucleoside analog, 4-FlU, was identified to effectively inhibit SFTSV in vitro. SFTSV-Nluc mimicked the replication characteristics and localization of SFTSVwt in counterpart model mice. Bioluminescence imaging of SFTSV-Nluc allowed real-time visualization and quantification of SFTSV replication in the mice. 4-FlU was demonstrated to inhibit the replication of SFTSV with more efficiency than T-705 and without obvious adverse effect in vivo. Interpretation: The high-throughput screening system based on SFTSV-Nluc for use in vitro and in vivo revealed that a safe and effective antiviral nucleoside analog, 4-FlU, may be a basis for the strategic treatment of SFTSV and other bunyavirus infections, paving the way for the discovery of antivirals. Funding: This work was supported by grants from the National Key Research and Development Plan of China (2021YFC2300700 to L. Zhang, 2022YFC2303300 to L. Zhang), Strategic Priority Research Program of Chinese Academy of Sciences (XDB0490000 to L. Zhang), National Natural Science Foundation of China (31970165 to L. Zhang, U22A20379 to G. Xiao), the Science and Technology Commission of Shanghai Municipality (21S11903100 to Y. Xie), Hubei Natural Science Foundation for Distinguished Young Scholars (2022CFA099 to L. Zhang).